Death is not the end: radiocarbon and histo-taphonomic evidence for the curation and excarnation of human remains in Bronze Age Britain. (October 2020) - Booth, Thomas J.; Brück, Joanna
Abstract: Abstract : Cremated and unburnt human remains have been recovered from a variety of British Bronze and earliest Iron Age archaeological contexts ( c . 2500–600 BC). Chronological modelling of 189 new and extant radiocarbon dates from a selection of these deposits provides evidence for the curation of human remains for an average of two generations following death, while histological analysis of bone samples indicates mortuary treatment involving both excarnation and the exhumation of primary burials. Curated bones came from people who had been alive within living or cultural memory, and their power probably derived from relationships between the living and the dead.